Psychological distress associated with cancer screening: A systematic review. Issue 20 (22nd August 2017) - Chad‐Friedman, Emma; Coleman, Sarah; Traeger, Lara N.; Pirl, William F.; Goldman, Roberta; Atlas, Steven J.; Park, Elyse R.
Abstract : BACKGROUND: Current national cancer screening recommendations include the potential risk of psychological harm related to screening. However, data on the relation of psychological distress to cancer screening is limited. The authors conducted a systematic review to assess psychological distress associated with cancer screening procedures. METHODS: Studies that administered measures of psychological distress between 2 weeks before and 1 month after the screening procedure were included. RESULTS: In total, 22 eligible studies met criteria for review, including 13 observational trials and 9 randomized controlled trials. Eligible studies used a broad range of validated and unvalidated measures. Anxiety was the most commonly assessed construct and was measured using the State Trait Anxiety Inventory. Studies included breast, colorectal, prostate, lung, and cervical screening procedures. Distress was low across procedures, with the exception of colorectal screening. Distress did not vary according to the time at which distress was measured. None of the studies were conducted exclusively with the intention of assessing distress at the time of screening. CONCLUSIONS: Evidence of low distress during the time of cancer screening suggests that distress might not be a widespread barrier to screening among adults who undergo screening. However, more studies are needed using validated measures of distress to further understand the extent to which screening may elicit psychological distress and impede adherence to national screening recommendations. Cancer 2017;123:3882‐94 . © 2017 American Cancer Society . Abstract : Current national cancer screening recommendations include the potential risk of psychological harm related to screening. This systematic review assesses psychological distress associated with cancer screening across breast, colorectal, prostate, lung, and cervical screening procedures.